2021
DOI: 10.1016/j.amsu.2021.102406
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glutathione as adjuvant therapy on levels of TNF-α and IL-10 in wistar rat peritonitis model

Abstract: Background Peritonitis is the second most common cause of severe sepsis that associated with a significant mortality rate. Due to a large gap of newer antibiotics innovation and antibiotic resistance emergence, the use of antioxidant has a possible alternative as adjuvant therapy in peritonitis management. It has been studied that glutathione as an alternative in the development of new anti-inflammatory effect. Thus, the aim of this study was to evaluate the levels of TNF-α and IL-10 after glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Elevated levels of these cytokines were observed in CP-based treatment, and their attenuation has the potential to ameliorate renal injury [44,45]. It also a known fact that GSH is one of the most potent antioxidants and has demonstrated anti-inflammatory properties together with modulation of many inflammatory markers to control inflammation [46]. In the present study, the CP group showed elevated levels of the IL-1β serum concentration and upregulation of the NF-KB (Figures 6 and 8) concentration inside renal tissue at similar levels to the reported data, as compared to the normal group of animals [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of these cytokines were observed in CP-based treatment, and their attenuation has the potential to ameliorate renal injury [44,45]. It also a known fact that GSH is one of the most potent antioxidants and has demonstrated anti-inflammatory properties together with modulation of many inflammatory markers to control inflammation [46]. In the present study, the CP group showed elevated levels of the IL-1β serum concentration and upregulation of the NF-KB (Figures 6 and 8) concentration inside renal tissue at similar levels to the reported data, as compared to the normal group of animals [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…In sepsis, glutathione has emerged as a significant determinant of cytokine production. Studies indicate that glutathione exhibits potent anti-inflammatory effects by reducing the levels of pro-inflammatory cytokines such as TNF-α and IL-1β [ 25 ]. Moreover, glutathione-induced immune-stimulatory activity fosters the polarization of M1-like macrophages, potentially facilitated by ROS-scavenging antioxidants, thus influencing cytokine production and immune responses [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…The acquired data of Prior Knowledge, Emotional Intelligence, Motivation and Mathematical Communication from the result of filling out the surveying test, the normality test examined by applying SPSS, this test functioned as prerequisite to assign which test was properly used to decide hypothesis. Normality test employed with Saphiro-Wilk test, which was executed to see whether normal or not of a data with minor sample (Junita et al,2021).…”
Section: Normality Testmentioning
confidence: 99%